Determinan Minat Berkarir Sebagai Akuntan Publik: Peran Moderasi Asas Kemandirian - Sri Ayem; Hasfaika Meiyani Kamaruddin (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2025)
Past investigate has recognized the components of career interest in becoming a public accountant independently without considering the directing impact of the principle of independence as one of the values of the Tamansiswa teachings. This study tests the hypothesis of the impact of financial rewards, professional training, perceptions of the public accounting profession on career interest in getting to be a public accountant and how the principle of independence moderates these factors. Study with a quantitative approach through purposive sampling method and a sample of accounting students at colleges that have a CPA Test Center within the DI Yogyakarta range then obtained 149 questionnaire respondents. Study information were analyzed with t-test, F test, coefficient determination test (R2) and moderated regression analysis (MRA). This study found that financial rewards, professional training and perceptions of the public accounting profession had a positive impact on career interest in getting to be a public accountant. The principle of independence as a mediator succeeds in moderating by strengthening the relationship between perceptions on career interest in becoming a public accountant, but cannot moderate the relationship between financial rewards and professional training on career interest in getting to be a public accountant.